Prophet Muhammad's daily lifestyle and its scientfic indications : an analytical study of Al-Shama'il Al- Muhammadiyyah - Khafizatunnisa' binti Jaapar (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
The main purpose of this study is to explore the greatness and purity of Prophet Muhammad's (s.a.w.) way of life and to analyze its significance for today's life from scientific perspective. There are numerous ahadith that detailed the everyday activities of the Prophet Muhammad s.a.w., yet the main source of hadith for this study is derived from Imam Tirmidhi's Al-Shama'il al-Muhammadiyyah which covers ahadith on the traits and the daily activities of the Prophet s.a.w. In this study, the hadith that concerns any given activity will first be stated and then it would go under the process of critical evaluation of its chain of narrators and the texts of ahadith, which will follow scientific value and impact of all given ahadith. The result of this study shows that almost all ahadith in Al-Shama'il al-Muhammadiyyah are 'sound' or 'acceptable' ones, though at times, Imam Tirmidhi quoted some 'weak' ahadith, and at rare cases, the 'extremely weak' ones. He quoted them due to its extensive benefits and sound meaning. There is no doubt that the discoveries made by the scientists of the past and the present prove that every act performed by Prophet Muhammad s.a.w. contains remarkable benefits for the maintenance and improvement of the human health. True devotion to the Sunnah of the Prophet s.a.w. would guarantee one balanced spiritual development and sound physical growth.